An efficient binary cathode interlayer for large-bandgap non-fullerene organic solar cells. Issue 20 (7th May 2019) - Yin, Qingwu; Zhang, Kai; Zhang, Long; Jia, Jianchao; Zhang, Xi; Pang, Shuting; Xu, Qing-Hua; Duan, Chunhui; Huang, Fei; Cao, Yong
Abstract : A binary cathode interlayer with both efficient charge extraction and transportation properties for large-bandgap non-fullerene OSCs. Abstract : With the rapid development in large-bandgap non-fullerene acceptors, the energy level mismatch between the cathode interlayer (CIL) and the acceptors becomes severe. Herein, we carefully investigate the influence of interlayers with different lowest unoccupied molecular orbital (LUMO) levels on the performance of non-fullerene organic solar cells (OSCs), and observe that the energy level alignment between interlayers and acceptors plays a crucial role in achieving high open circuit voltage ( V oc ) and efficient charge extraction. Meanwhile, we find that the electron extraction and transport abilities of the CIL can be tuned by blending two CIL materials together with different ratios (named binary CIL). Based on these findings, efficient single-junction, double-junction and triple-junction homo-tandem OSCs based on a large-bandgap non-fullerene acceptor and binary CIL with an ultrahigh V oc of 1.22 V, 2.39 V and 3.21 V are demonstrated. The high V oc of tandem OSCs further ensure their application in solar-energy-driven water splitting. This study offers a new strategy to extend the application of CILs, and helps to develop efficient and thick CILs for printed large-area non-fullerene OSCs.